Exploring the Substrate Scope of Baeyer–Villiger Monooxygenases with Branched Lactones as Entry towards Polyesters. (29th November 2017) - Delgove, Marie A. F.; Fürst, Maximilian J. L. J.; Fraaije, Marco W.; Bernaerts, Katrien V.; De Wildeman, Stefaan M. A.
Abstract: Baeyer–Villiger monooxygenases (BVMOs) are biocatalysts that are able to convert cyclic ketones into lactones by the insertion of oxygen. The aim of this study was to explore the substrate scope of several BVMOs with (biobased) cyclic ketones as precursors for the synthesis of branched polyesters. The product structure and the degree of conversion of several biotransformations were determined after conversions by using self‐sufficient BVMOs. Full regioselectivity towards the normal lactones of jasmatone and menthone was observed, whereas the oxidation of other substrates such as α, β‐thujone and 3, 3, 5‐trimethylcyclohexanone resulted in mixtures of regioisomers. This exploration of the substrate scope of both established and newly discovered BVMOs towards biobased ketones contributes to the development of branched polyesters from renewable resources. Abstract : Branching out : The substrate scope of several Baeyer–Villiger monooxygenases (BVMOs) is explored towards (terpene‐based) branched ketones. This comparative study shows that BVMOs have potential for the synthesis of branched lactones as precursors for polyesters with tuned functionalities.